PENGARUH SERVICE DAN PROMOSI TERHADAP KEPUASAN NASABAH PADA TRUST SEBAGAI VARIABEL INTERVENING DI BPR LAKSANA ABADI SUNGGAL - Sri Ramadhani Br. Ginting; Ihsan Effendi; Wan Rizca Amelia (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2020)
This study aims to learn about "The Effect of Services and Promotions on Customer Satisfaction in Interventions as Variables in BPR Laksana Abadi Sunggal. This type of research is associative research that is research that discusses the relationship between two variables. The population in this study is the entire research of BPR Laksana Abadi Sunggal. The technique used in this study uses probability sampling or random sampling with representatives, so the number of this study was 100 respondents taken from part of the funds at BPR Laksana Abadi Sunggal. Based on the results of this research, it can be seen that service and promotion variables are positive and significant to Customer Satisfaction in Trustworthiness as an Intervening Variable in BPR Laksana Abadi Sunggal.